Brain Activation Time-Locked to Sleep Spindles Associated With Human Cognitive Abilities - Fang, Zhuo; Ray, Laura B.; Owen, Adrian M.; Fogel, Stuart M. (Frontiers in Neuroscience, 2019)
Simultaneous EEG-fMRI studies have revealed brain activations time-locked to spindles. Yet, the functional significance of these spindle-related brain activations is not understood. EEG studies have shown that inter-individual differences in the electrophysiological characteristics of spindles (e.g., density, amplitude, duration) are highly correlated with “Reasoning” abilities (i.e., “fluid intelligence”; problem solving skills, the ability to employ logic, identify complex patterns), but not Short-Term Memory, or Verbal abilities. Spindle-dependent reactivation of brain areas recruited during new learning, suggests night-to-night variations reflect offline memory processing. However, the functional significance of stable, trait-like inter-individual differences in brain activations recruited during spindle events are unknown. Using EEG-fMRI sleep recordings, we found that a subset of brain activations time-locked to spindles were specifically related to Reasoning abilities but were unrelated to Short-Term Memory or Verbal abilities. Thus, suggesting that individuals with higher fluid intelligence have greater activation of brain regions recruited during spontaneous spindle events. This may serve as a first step to further understand the function of sleep spindles and the brain activity which supports the capacity for Reasoning.